Emotional and Motivational School Readiness of Six-Year-Old Children and Parental Support in Mothers’ Assessments - Michalska, Paulina; Szymanik-Kostrzewska, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The aim of the research was to determine the readiness of 6-year-old children to start school education, especially the emotional and motivational readiness and the level of support for this readiness in the assessment of mothers. 131 mothers of 63 girls and 68 boys participated in the research. Three proprietary research methods were used: the Child’s Emotional and Motivational Readiness Questionnaire for the Parent, the Parent’s Child’s School Readiness Assessment Questionnaire – version 3 and the Parent’s Questionnaire for Supporting the Child’s Emotional and Motivational Readiness. Both the level of school readiness of children and the level of support were assessed by the surveyed mothers as high. Numerous positive correlations were observed between the manifestations of school readiness and the manifestations of mothers’ support. Supporting the development of the child’s autonomy and independence turned out to be the predictor of the child’s emotional and motivational readiness.